2006
DOI: 10.1073/pnas.0604392103
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuins deacetylate and activate mammalian acetyl-CoA synthetases

Abstract: Silent Information Regulator 2 (Sir2) enzymes (or sirtuins) are NAD ؉ -dependent deacetylases that modulate gene silencing, aging and energy metabolism. Previous work has implicated several transcription factors as sirtuin targets. Here, we investigated whether mammalian sirtuins could directly control the activity of metabolic enzymes. We demonstrate that mammalian Acetyl-CoA synthetases (AceCSs) are regulated by reversible acetylation and that sirtuins activate AceCSs by deacetylation. Site-specific acetylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
646
2
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 723 publications
(654 citation statements)
references
References 50 publications
5
646
2
1
Order By: Relevance
“…Several lines of evidence showed that localization of SIRT1 in the cytoplasm is induced during apoptosis (Ohsawa and Miura, 2006;Jin et al, 2007). In addition, Hallows et al demonstrated that SIRT1 catalyses the deacetylation of Acetyl-CoA synthetases (AceCSs) in the cytoplasm (Hallows et al, 2006). In this study, we found that SIRT1 is localized in both the nucleus and cytoplasm in OV2008 and C13 ovarian cancer surface epithelial cells (Supplementary Figures S1 and S2).…”
Section: Discussionsupporting
confidence: 52%
“…Several lines of evidence showed that localization of SIRT1 in the cytoplasm is induced during apoptosis (Ohsawa and Miura, 2006;Jin et al, 2007). In addition, Hallows et al demonstrated that SIRT1 catalyses the deacetylation of Acetyl-CoA synthetases (AceCSs) in the cytoplasm (Hallows et al, 2006). In this study, we found that SIRT1 is localized in both the nucleus and cytoplasm in OV2008 and C13 ovarian cancer surface epithelial cells (Supplementary Figures S1 and S2).…”
Section: Discussionsupporting
confidence: 52%
“…SIRT3 functions as a protein deacetylase (Onyango et al, 2002;Schwer et al, 2002), and specifically targets K642 of the mitochondrial protein acetyl-CoA synthetase 2. Deacetylation of acetyl-CoA synthetase 2 activates the enzyme and promotes the production of acetyl-CoA (Hallows et al, 2006;Schwer et al, 2006). Several genetic studies have linked SIRT3 to aging, including in humans (Rose et al, 2003;Glatt et al, 2007).…”
Section: Mitochondrial Sirtuins: Sirt3 Sirt4 and Sirt5mentioning
confidence: 99%
“…Rapid progress in the discovery and functional analysis of an increasing number of nuclear enzymes involved in protein lysine acetylation and deacetylation, histone acetyltransferases (HATs) and histone deacetylases (HDACs), respectively, have demonstrated that these enzymes, independently of transcription, can control some of the basic cellular processes such as protein stability (reviewed in Caron et al, 2005). Moreover, it is now clear that acetylation is not an exclusive modification of nuclear proteins, since many cytoplasmic proteins, including a significant subset of mitochondrial proteins, have recently been shown to bear lysine acetylation (Cohen et al, 2004;Dihazi et al, 2005;Iwabata et al, 2005;Kovacs et al, 2005;Hallows et al, 2006;Kim et al, 2006;Schwer et al, 2006). The regulation of these acetylations and the determination of their functional significance now constitute a real challenge for biologists.…”
Section: Introductionmentioning
confidence: 99%